PROSES PENINGKATAN KINERJA KARYAWAN PADA PT. PULAU KENCANA RAYA DI JAKARTA - Agus Salim (POLITEKNIK LP3I JAKARTA, 2017)
ABSTRACT The success of a company in achieving its goals depends on how the company manages and prepares its human resource management. A company will certainly get many challenges and problems both from outside and from within the company itself. In the achievement of corporate objectives, of course, the company must improve the performance of existing human resources by providing motivation to be used as an encouragement in doing a job in the company. The purpose of this study to determine the process of improving employee performance at PT. Pulau Kencana Raya, The process of improving employee performance at PT. Pulau Kencana Raya is implemented based on 3 (three) tahapa Target Achievement, Performance Assessment and Provision of motivation. This research uses descriptive qualitative research method, the results of research to provide recommendations to the company in providing motivation so that employees will feel valued and noticed by the company and employees will be able to provide a better contribution again to the company. Keyword : Keyword:, Employee’s Performance, Motivation and Target